C-Reactive Protein to Albumin Ratio in Colorectal Cancer: A Meta-Analysis of Prognostic Value - Qiang-ping Zhou; Xiu-jiang Li (SAGE Publishing, 2019)
Background: The relationship between pretreatment C-reactive protein to albumin ratio (CAR) and colorectal cancer (CRC) prognosis has been extensively studied in various tumors. However, little is known on CAR and its association with prognosis in CRC. This study aims to investigate the prognostic value of pretreatment CAR in CRC. Methods: We conducted a systematic search of MEDLINE, EMBASE, and Cochrane Library databases for eligible studies evaluating the associations of CAR with survival and/or clinicopathology of CRC. Overall survival (OS), disease-free survival (DFS), relapse-free survival (RFS), and clinicopathological features were synthesized and compared. Results: Nine studies including 3431 patients were analyzed in this meta-analysis. Pooled results showed that elevated pretreatment CAR was associated with poor OS (pooled hazards ratio [HR]: 2.18, 95% confidence interval [CI]: 1.70-2.78, P < .001) and DFS/RFS (pooled HR: 2.36, 95% CI: 1.40-3.98, P < .001). Moreover, elevated pretreatment CARs were correlated with male patients, large tumor diameter, late III-IV tumor node metastasis stage tumors, high serum carcinoembryonic antigen and carbohydrate antigen 19-9, and presence of lymphatic invasion and venous invasion. Conclusion: Elevated pretreatment CAR could be an adverse prognostic indicator in patients with CRC.